Designing interfaces - Tidwell, Jenifer (O'Reilly, 2011)
This text offers advice on creating user-friendly interface designs - whether they're delivered on the Web, a CD, or a 'smart' device like a cell phone. It presents solutions to common UI design problems as a collection of patterns - each containing concrete examples, recommendations, and warnings.